ANALISIS KEMUDAHAN DAN PERSEPSI RISIKO SERTA DAMPAK PADA KEPUASAN PENGGUNAAN MOBILE BANKING - Anwar, Anwar; Riza, Akmal (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of ease and perceived risk on the satisfaction of using mobile banking. This type of causal associative research with a quantitative approach, a sample of 36 respondents using the Accidental Sampling technique for entrepreneurs in Aceh who make transactions every day using BSI Mobile. Primary data sources by distributing questionnaires using Googleform and data analysis methods or proving the hypothesis using the OLS model with SPSS version 28.0. The results of the study found that the ease of using BSI Mobile has a significant effect on the satisfaction of entrepreneurs conducting m-banking transactions, while perceived risk has no effect on the satisfaction of entrepreneurs using m-banking.Keywords: Ease and perceived risk, customer satisfaction